PERFORMANCE ALALYSIS OF VILLAGE APPARATUS IN PROVIDING SERVICE TO THE BONGOIME VILLAGE COMMUNITY - Meylan Ibrahim; Djamila Podungge; Nuzmerini Rauf (LP2M Universitas Bina Mandiri Gorontalo, 2024)
The research aims at investigating the formance of village officials in bongoime village. 2) to find out the inhibiting factors in improving the pormance of bongoime village apparatus The method in this research used qualitative method with data collection techniques of observation, interviews and documentation.The research results show that 1) The performance of Bongoime village officials has many jobs that are in accordance with their respective main duties and functions and have good jobs. Apart from that, complete and be accountable for every task that originates from local government regulations regarding what work must be done in the village with the amount of work that can be completed within the predetermined time, namely starting work at 08.00 in the morning until 04.00 in the afternoon. Each village apparatus is always controlled and evaluated by the leadership based on their respective fields/expertise. Each village apparatus is always controlled and evaluated by the leadership based on their respective fields/expertise. 2) The inhibiting factor in improving the performance of Bongoime village officials is having maximum effort to complete the work with organizational support, the organization provides facilities for its employees including training and development, equipment and technology, performance standards and management as well as good coworkers. This can be seen from efforts to approach the community, outreach to the youth in the community so that every work that will be planned by the village is in accordance with proposals made by the community.